KESULITAN BELAJAR PESERTA DIDIK KELAS V SDN INPRES 1 TONDO - Indriastuti, Danti; Boroallo, Rangga Putera; Nafisya, Ifka (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Learning difficulties in students refer to conditions where they experience obstacles or difficulties in understanding subject matter, following the learning process, or achieving the expected academic goals, even though they have sufficient potential. The aim of this research is to determine the learning difficulties of grade 5 students at SD Impress 1 Tondo. This research is a quantitative descriptive research. A total of twenty fifth graders from SD Inpres 1 Tondo were part of the sample that was selected using a population sampling method. Questionnaires, interviews, and records were the means of data collecting. The results of the questionnaire data analysis on Class V learning issues at Impress 1 Tondo Elementary School indicate that there are two main variables, internal and external, that contribute to these difficulties. contributing element. Yes, I get it. contributing element. With a score of 60 and medium-range criteria, motivation is the internal component that significantly impacts, followed by study habits which is 50%, medium category, interest which is 46.67, and finally attitude 43.33%. The school environment as an external factor has the highest value, namely 50, while the home environment has a value of 46.67, both of which are included in the medium category. In conclusion, the learning difficulties of fifth grade students at SD Impress 1 Tondo are significantly influenced by motivational factors and the school environment.